Oral precancer : diagnosis and management of potentially malignant disorders - Thomson, Peter James (Chichester, West Sussex : Wiley-Blackwell, 2012)
'Oral Precancer is a preeminent new book that compiles recent research on precancer conditions of the oral cavity and their specific application to the dental field. In addition to providing a scientific and evidence-based survey of the disparate sources of oral precancer research, this book presents practical information for dental practitioners. Written by a prominent researcher in the field, Oral Precancer furnishes its readers with a balanced approach to this highly topical subject'--Provided by publisher.
Keywords: Mouth Neoplasms; Precancerous Conditions